Phishing Website Detection Technique Using Machine Learning - Nurul Amira, Mohd Zin (2022)
The Internet has emerged as an indispensable tool in both our personal and professional life in our modern day. The Internet is crucial not just for individual users, but also for businesses, since enterprises who provide online commerce may gain a competitive advantage by serving customers all over the globe. This makes the Internet essential for everyone who uses it. The Internet enables companies to conduct effective e-commerce with customers located all over the globe without regard to the geographical constraints of individual markets. As a direct consequence of this, the number of customers who make their purchases over the internet is quickly increasing. Daily, transactions totaling hundreds of millions of dollars are carried out through the Internet. These dishonest individuals were tempted to participate in their fraudulent endeavors by this quantity of money. Internet users may be vulnerable to a wide variety of web threats because of this fact. These threats may result in monetary loss, fraudulent use of credit cards, the loss of personal data, potential damage to the reputation of a brand, and customer mistrust in e-commerce and online banking. Because of this, doing financial transactions through the Internet is fraught with potential risks. Phishing is a sort of cyber threat that may be defined as the practice of imitating a genuine website for the purpose of stealing sensitive information such as usernames, passwords, and credit card numbers. This article will devote considerable space to discussing the topic of phishing. In addition, we provide an update on the most recent findings from research conducted on the topic. In addition, we want to discover recent advancements in phishing and preventative measures, as well as carry out a full analysis and review of this research, all with the goal of bridging the knowledge gap that still exists in this field. This research focuses on strategies for detecting phishing attacks through the internet rather than ways for detecting attacks via email.